Knowledge on Chest Tube Drainage among Nurses Working in a Teaching Hospital of Pokhara - Pradhan, Muskan; Gurung, Bishnu (Journal of Nursing and Health Sciences Nepal, 2025)
Introduction: Chest tube drainage is one of the most important nursing procedures because patientswho require chest tubes are usually seriously ill and require advanced nursing care. Inefficient nursing care of chest drains may be associated with unacceptable and sometimes life-threatening complications. Therefore, nurses must have sufficient knowledge to make the right decisions at critical points, minimize complications, and provide effective and quality care. This study aimed to identify the level of knowledge on chest tube drainage among nurses and to determine association level of knowledge and selected variables. Methods: A descriptive cross-sectional study was conducted among nurses at the Gandaki Medical College Teaching Hospital and Research Center in Pokhara. Simple random sampling technique was used, to select 117 nurses in the study. Data was collected using self-administered structured questionnaire and entered into SPSS version 22, Descriptive statistics (frequency, percentage, mean, and standard deviation) were used to describe the variables. Inferential statistics (chi-square test) was used to determine the association between the level of knowledge on chest tube drainage and selected background variables. Results: The findings of the study reported that 57.3% of the nurses had satisfactory knowledge, while 42.7 percent had unsatisfactory knowledge on chest tube drainage. Similarly, there was a significant association between the level of knowledge with working area (p value= 0.001) and working experience (p value= 0.018). Conclusion: This study concludes that less than half of the nurses have unsatisfactory knowledge on chest tube drainage. Hence, it is necessary to provide continuing education and training to improve nurses’ knowledge of Chest Tube Drainage.